Men, women and nation: media representation during the Stroessner dictatorship in Paraguay (1959) - Orué Pozzo, Aníbal (2017)
Assuming as structural axis the newspaper El País content’s (September-December, 1959) related to the death of the journalist Bernardo Aranda, the article discuss from a gender perspective, representations and imaginaries regarding how this media introduce the idea of nation. The text selected two semantic matrix associated with: i) youth and rock and roll music, and ii) Discipline and virile postures, and develop an interpretation of how and in what specific way this idea of nation building is manufactured.